Comparison of 2D Hybrid Simulational and Experimental Results for Dual-Frequency Capacitively Coupled Argon Plasmas - 毕振华 徐翔 刘永新 蒋相占 陆文琪 王友年 (Plasma science & technology, 2011)
A two-dimensional hybrid simulation scheme is proposed to study the characteristics of dual-frequency （DF） capacitively coupled plasma （CCP） discharge based on the geometry of real device. Given the experimental parameters for argon plasma, the output from the fluid module such as ion density, number flux, electron temperature and the Monte-Carlo collision （MCC） results of ion energy distribution function （IEDF） as well as electron energy distribution function （EEDF） are obtained and discussed in detail. A novel complete floating double probe is designed to measure both density and temperature of electron and a quadrupole mass spectrometer is also equipped for IEDF investigations. The measurements on the density of bulk plasma, electron temperature and IEDF agree well, qualitatively, with the simulated results. A comparison with experimental results indicates that, since the structure of real device is taken into account, this model is capable of describing the global dynamic characteristics occurred in DF-CCP and presenting more reliable results than the model with an ideal chamber structure.